Carbide-derived carbon as an extraordinary material for the removal of chromium from an aqueous solution. (November 2022) - Almanassra, Ismail W.; Al-Ansari, Tareq; Ihsanullah, Ihsanullah; Kochkodan, Viktor; Chatla, Anjaneyulu; Atieh, Muataz Ali; Shanableh, Abdallah; Laoui, Tahar
Abstract: In the present work, the adsorptive removal of chromium (Cr) from water by carbide-derived carbon (CDC) was investigated. The morphology and structure of the CDC were characterized by using FTIR, SEM, TEM, XRD, and N2 adsorption-desorption measurements. The effect of adsorption parameters including contact time, initial Cr concentration, temperature, initial solution pH, and CDC dosage was examined on the removal of Cr ions. The kinetic analysis revealed that the experimental data on the removal of Cr ions on CDC is well correlated with the pseudo-second order kinetic model (with R 2 > 0.999), while the equilibrium data were fitted by the Redlich-Peterson isotherm model (with R 2 > 0.992). The Langmuir and Sips models were also in good compliance with the equilibrium data, indicating a monolayer coverage of Cr ions onto the CDC surface with some heterogeneous active adsorption sites. The CDC revealed a notable Langmuir adsorption capacity of 159.1 mg/g for Cr ions at pH 6 and room temperature. The thermodynamic analysis illustrated that the Cr ions elimination by CDC is a feasible adsorption process and endothermic in nature. After five adsorption/desorption cycles, less than 18% reduction in the adsorption capacity was obtained indicating the stability and reusability of the CDC. Moreover, the CDC demonstrated an excellent potential in removing the Cr ions from real brackish water. According to the adsorption data, both physical and chemical adsorption processes occurred, and the adsorption was mainly controlled by electrostatic interactions with a possible reduction of hexavalent Cr to trivalent Cr at acidic conditions. Graphical abstract: Image 1 Highlights: The CDC was employed for the removal of chromium ions from an aqueous solution. A maximum capacity of 159.1 mg/g for Cr ions was observed. The adsorbent maintained a removal efficiency of >80% of Cr after 5 adsorption/desorption cycles. Both chemical and physical adsorption was found to control the adsorption process.